Performance of Certified Physical Education Teacher (Review of Self Concept and Work Motivation) (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
Physical education teacher is certified expected to have good performance. Good or bad teacher performance depends on the self-concept and motivation of the teacher in carrying out its duties. This study aims to obtain a description of self-concept, work motivation, and performance of certified Physical education teachers in the working group of Physical education teachers in Bonang Region, Demak District. This research uses a qualitative method with phenomenology design. Data collection techniques use interviews, observations, and documents. Research subjects of 3 certified Physical education teachers residing in the Teacher Working Group Bonang, secondary data are colleagues and principals. Methods of data collection in the form of observation guidelines and interview guidelines. Data analysis techniques include data reduction, data presentation, and withdrawal of conclusions/verification. It is concluded that the most important factor of self-concept influencing the performance of the subject is the self-assessment factor. While the most important factor of work motivation is internal motivation. It is recommended for the subjects to cultivate positive self-concept, the spirit of work, and the spirit of creativity and activity.